Making music together, or improvisation and its others - Cook, Nicholas (Jazz Research Journal, 2004)
I can focus my topic through two diametrically opposed quotations concerning the relationship between jazz and the music of the Western ’art’ tradition. One the one hand, Ingrid Monson (1996:74) writes that ’meaningful theorizing about jazz improvisation at the level of the ensemble must take the interactive, collaborative context of musical invention as a point of departure. This context has no parallel in the musical practice of Western classical composers of the common practice period’. On the other hand, Alfred Schutz (1964:177) writes that ’there is no difference in principle between the performance of a string quartet and the improvisations at a jam session of accomplished jazz players’. Reconciliation is impossible; the standoff could hardly be more complete.